IMPLEMENTASI KRIPTOSISTEM KURVA ELIPTIK DENGAN PERTUKARAN KUNCI DIFFIE-HELLMAN PADA DATA AUDIO DIGITAL - Anita Ahmad Kasim (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2010)
Technology not only allows information submitted in the form of text, but also in the form of images, audio or video.  However,  the  use  of  digital  audio  data  is  not  necessarily  improves  the  security  of  the  message. Various  attack  techniques  emerged  so  others  can  know  the  confidential  information  contained  in  digital audio  messages.  One  attempt  to  provide  information  that  can  be  done  is  a  cryptographic  system  or cryptosystem. In the elliptic curve equation are the values that can be used as a private key and public key to  encrypt  the  data  in  this  form  of  audio.  Audio  data  will  be  processed  on  the  secure  encryption  and decryption  using  elliptic curve cryptography  with  Diffie-Hellman  key  exchange. Parameters  and  variables contained in the curve equation would be calculated to determine the shared secret key to be used in both encryption and decryption process audio. The conditions before the encrypted audio data are audible. The result of encrypting the audio data to produce a new audio is not clear. Decryption process causes the data back to the original audio data so that the second audio data can be heard clearly. Attack man in the middle of this process can’t decrypt the encrypted audio file. File decryption results may not be tuned so that the audio file will be secure and can only be heard by the user encryption and decryption that really has the right combination of keys that user actual encryption and decryption.